Preparation of thin films with densely aggregated zinc phthalocyanine nanowires oriented uniaxially on friction-transferred polytetrafluoroethylene template - Yuki Chiyonobu; Yasuko Koshiba; Kana Tomosada; Takuya Matsumoto; Shohei Horike; Takashi Nishino; Kenji Ishida; Masahiro Funahashi (Discover Polymers)
Abstract One-dimensional nanostructures of organic semiconductors exhibit distinctive optical and electrical properties. In this study, thin films containing densely aggregated, uniaxially oriented zinc phthalocyanine (ZnPc) nanowires are fabricated through vapor deposition on polytetrafluoroethylene (PTFE) friction-transferred films as orientation-inducing templates. The aggregation behavior of the ZnPc molecules depends on the substrate temperature (T s) during deposition and the film thickness. Full-coverage aggregated ZnPc nanowires aligned parallel to the friction direction are formed in a film with a thickness of 20 nm deposited at T s = 120 °C. Within the ZnPc nanowires, α-ZnPc crystals are aligned with the b-axis along the direction of nanowire growth and the a-axis perpendicular to the substrate. This indicates that the longitudinal direction of the ZnPc nanowires corresponds to the π‒π stacking direction of ZnPc molecules. A model detailing the growth of ZnPc nanowires on a PTFE film is proposed, elucidating the crystal growth and orientation through graphoepitaxial and epitaxial-like mechanisms. The PTFE friction-transferred film is demonstrated to be an effective template for the growth of aligned ZnPc nanowires. The uniaxially oriented, full-coverage ZnPc nanowire thin film fabricated on the PTFE template showed anisotropic electrical properties.